The Effect of Study Abroad on Grammatical Accuracy of Indonesian Students’ Oral and Written Performance - Kristian Adi Putra (Master Program in Linguistics, Diponegoro University, 2013)
This correlational study investigates the effect of study abroad of two exchange students (SA) from Indonesia in public schools in the United States on their grammatical accuracy as compared to the oral and written performance of two first year college students through formal instruction (FI) in Indonesia never experiencing living in L2 environment. Speech samples were elicited through interview via-Skype, while writing samples were obtained through writing task. The result of this study shows that in oral and written performance, SA participants used more accurate grammar than FI participants. However, SA participants were more accurate in using the three tenses in writing (90%) than in speaking (87%), while FI participants showed different result, i.e. their grammatical accuracy of speaking (78%) was higher than that of writing (76%).Studi korelasional ini meneliti efek studi di luar negeri untuk dua siswa Indonesia program pertukaran (SA) di sekolah negeri Amerika Serikat dalam hal ketepatan gramatikal yang dibandingkan dengan ketrampilan lesan dan tulis mahasiswa tahun pertama melalui instruksi formal (FI) di Indonesia yang belum pernah tinggal di lingkungan bahasa kedua. Sampel ketrampilan lesan dikumpulkan lewat wawancara via Skype, sedangkan sampel ketrampilan tulis diperoleh melalui tugas mengarang. Hasil penelitian ini menunjukkan bahwa dalam ketrampilan lesan dan tulis, akurasi gramatikal peserta SA lebih tinggi daripada peserta FI. Namun demikian, peserta SA lebih akurat dalam menggunakan tiga kala dalam mengarang (90%) daripada penggunaan kala dalam berbicara (87%), sementara peserta FI menunjukkan hasil yang berbeda, yaitu akurasi gramatikal berbicara (78%) lebih tinggi daripada akurasi gramatikal mengarang (76%).